Kedudukan Program Subsidi Bahan Bakar Minyak dan Penghapusannya dalam Perspektif Teori Negara Kesejahteraan - Petrus Pidi Seda; Supriyadi Supriyadi; Samsul Wahidin (Postgraduate University of Merdeka Malang, 2020)
Indonesia is a country that adopts the concept of a welfare state. The welfare state refers to the role of the government which is responsible for managing and organizing the people's economy. The state is expected to be able to carry out its responsibility to ensure the availability of basic rights welfare services for its citizens. The provision of subsidies is a government program to ensure the welfare of the people. The research objective is to examine the position of the subsidy program from the perspective of the welfare state and the elimination of fuel subsidies by the government as a welfare state. This research is normative legal research, which deals with the policy of eliminating fuel subsidies from the perspective of the welfare state. The approach used is statutory and conceptual. In a legal concept, the position of the subsidy policy is to help improve people's welfare. The removal of fuel subsidies is a government action that is following the concept of the welfare state because the use of BBM is not included in the basic needs of the community which must be subsidized or intervened by the government.AbstraksIndonesia merupakan negara yang menganut konsep negara kesejahteraan. Negara kesejahteraan mengacu pada peran pemerintah yang bertanggungjawab dalam mengelola dan mengorganisasikan perekonomian masyarakat. Negara diharapkan mampu menjalankan tanggung jawabnya untuk menjamin ketersediaan pelayanan kesejahteraan hak-hak dasar bagi warganya. Pemberian subsidi merupakan program pemerintah untuk menjamin kesejahteraan rakyat. Tujuan penelitian adalah untuk mengkaji kedudukan program subsidi dalam perspektif negara kesejahteraan, dan penghapusan subsidi BBM oleh pemerintah sebagai negara kesejahteraan. Penelitian ini merupakan penelitian hukum normatif, yang berhubungan dengan kebijakan penghapusan subsidi BBM dalam perspektif negara kesejahteraan. Pendekatan yang digunakan adalah pendekatan perundang-undangan dan konseptual. Secara konsep hukum, kedudukan kebijakan subsidi untuk membantu meningkatkan kesejahteraan rakyat. Penghapusan subsidi BBM merupakan tindakan pemerintah yang telah sesuai dengan konsep negara kesejahteraan karena penggunaan BBM tidak termasuk dalam kebutuhan dasar masyarakat yang harus disubsidi atau diintervensi oleh pemerintah. DOI: https://doi.org/10.26905/mlj.v1i2.5533